PENGARUH PENAMBAHAN NaOH PADA WATER DEGUMMING DAN ALKALI REFINING TERHADAP KUALITAS RED PALM OIL OLEIN (RPOO) - Ilham Agus Saputra; Budiyanto Budiyanto; Devi Silsia (BPFP Faperta UNIB, 2023)
Red Palm Oil Olein (RPOO), obtained from Crude Palm Oil (CPO) processing, can be a potential source of provitamin A due to its high carotene. Water degumming and Alkali refining are alternative methods that are not widely used to remove gum and Free Fatty Acids (FFA) in making RPOO with relatively low heating temperatures. This study aims to determine the effect of increasing the amount of NaOH during neutralization on RPOO yield, FFA levels, β-carotene content, vitamin A, and preference level for RPOO. This study used Complete Randomized Design (CRD) with one treatment factor, namely variations in the addition of the amount of NaOH. The results showed that the variation of the addition of NaOH had a significant effect on decreasing FFA RPOO to range from 0.24 to 0.07. The content of β-carotene produced ranges from (635.87 to 645.54 ppm) and the content of provitamin A ranges from (105.97 to 107.59 μgRE). In addition, the RPOO yield decreased with an increase in NaOH use, ranging from (53.24 to 42.26%). Organoleptic tests showed that adding NaOH significantly affects the level of liking for the color and aroma of RPOO. Increasing the use of NaOH in alkaline refining could produce RPOO with good quality, but at the same time, it could reduce the yield of RPOO produced.